Structural Based Screening of Antiandrogen Targeting Activation Function-2 Binding Site - Liu, Yangguang; Wu, Meng; Wang, Tianqi; Xie, Yongli; Cui, Xiangling; He, Liujun; He, Yang; Li, Xiaoyu; Liu, Mingliang; Hu, Laixing; Cen, Shan; Zhou, Jinming (Frontiers in Pharmacology, 2018)
Androgen receptor (AR) plays a critical role in the development and progression of prostate cancer (PCa). Current antiandrogen therapies induce resistant mutations at the hormone binding pocket (HBP) that convert the activity of these agents from antagonist to agonist. Thus, there is a high unmet medical need for the development of novel antiandrogens which circumvent mutation-based resistance. Herein, through the analysis of AR structures with ligands binding to the activation function-2 (AF2) site, we built a combined pharmacophore model. In silico screening and the subsequent biological evaluation lead to the discovery of the novel lead compound IMB-A6 that binds to the AF2 site, which inhibits the activity of either wild-type (WT) or resistance mutated ARs. Our work demonstrates structure-based drug design is an efficient strategy to discover new antiandrogens, and provides a new class of small molecular antiandrogens for the development of novel treatment agents against PCa.